Oligosaccharides and diet-related dilated cardiomyopathy in beagles - Bokshowan, Elise; Olver, T. Dylan; Costa, Matheus de O.; Weber, Lynn P. (Frontiers in Veterinary Science, 2023)
Introduction In 2018 the US Food and Drug Administration reported a potential link between grain-free, legume-containing dog foods and the development of canine dilated cardiomyopathy in atypical breeds. One hypothesis was that high oligosaccharide content in legumes reduced bioavailability of taurine, an amino acid with some previous links to canine dilated cardiomyopathy. Methods To address this hypothesis, in the present study, 8 Beagle dogs consumed four diets: a husbandry commercial dental diet, and three test diets formulated with either 30% rice (control), 30% pea (grain-free) or 30% rice with the addition of 1% raffinose (the predominant oligosaccharide found in peas). The study was conducted in a randomized, crossover design with 5 week feeding periods. Measurement of basic health parameters (weight, body condition score, complete blood cell count, chemistry panel), plasma amino acids, cardiac biomarkers (plasma N-terminal pro-brain natriuretic peptide (NT-proBNP) and cardiac-specific troponin I), fecal bile acids and echocardiographic exams were completed pre-study after feeding the husbandry diet as well as after each test feeding period. Results Echocardiography showed 9–11% reduction in ejection fraction and 17– 20% greater left ventricular end systolic volume with the husbandry diet compared to both grain-containing test diets. Concentrations of plasma NT-proBNP were 1.3–2 times greater after the husbandry diet compared to the grain-based diet, with the oligosaccharide and pea-based diets showing intermediate levels. Plasma taurine levels were unchanged across diets, while plasma methionine levels were highest and cysteine/cystine levels were lowest after dogs ate the husbandry diet. Discussion Results indicate that raffinose in the diet is sufficient, but not required to see an increase NT-proBNP, but did not induce any changes in cardiac function after 5 weeks of feeding. Whether this could progress to reduction in cardiac function with longer term feeding is uncertain. A reduced cardiac function along with the greatest increase in NT-proBNP was observed after feeding the husbandry diet that contained the highest amount of insoluble fiber but did not contain legumes or oligosaccharide. Further research into the impact of insoluble fiber in the dental diet is needed to support these novel observations.